Binding of saturated and unsaturated C6-hydrocarbons to the electrophilic anion [B12Br11]−: a systematic mechanistic study. Issue 36 (13th September 2022) - Ma, Xin; Rohdenburg, Markus; Knorke, Harald; Kawa, Sebastian; Liu, Judy Kuan-Yu; Aprà, Edoardo; Asmis, Knut R.; Azov, Vladimir A.; Laskin, Julia; Jenne, Carsten; Kenttämaa, Hilkka I.; Warneke, Jonas
Abstract : Highly reactive closed-shell molecular anions [B12 Br11 ] − spontaneously form covalent bonds with hydrocarbon molecules, including very unreactive alkanes, in the gas phase. Abstract : The highly reactive gaseous ion [B12 Br11 ] − is a metal-free closed-shell anion which spontaneously forms covalent bonds with hydrocarbon molecules, including alkanes. Herein, we systematically investigate the reaction mechanism for binding of [B12 Br11 ] − to the five hexane isomers yielding [B12 Br11 (C6 H14 )] −, as well as to cyclohexane and several hexene isomers (yielding [B12 Br11 (C6 H12 )] − ) using collision-induced dissociation (CID), infrared photodissociation spectroscopy (IRPD) and computational methods. CID of the different [B12 Br11 (C6 H14 )] − ions results in distinct fragmentation patterns dependent on the structure of the hexane isomer. The observed fragmentation reactions provide insights into the addition mechanism of [B12 Br11 ] − to hexane. Based on the observed CID patterns, we identified that either B–C bond formation through heterolytic C–C or C–H bond cleavages or B–H bond formation through heterolytic C–H cleavage occur dependent on the structure of the hexane isomer. Meanwhile, we observe identical CID spectra of adducts originating from isomers of C6 H12 . Spectroscopic investigations of adducts of 1-hexene and cyclohexane indicate the same product structure with an open C6 chain. Computational investigations evidenced that low lying transition states are present, which enable a ring opening reaction of cyclohexane when binding to [B12 Br11 ] − .